2005
DOI: 10.1063/1.2140847
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of magnetohydrodynamic turbulence at low magnetic Reynolds number

Abstract: Turbulent fluctuations in magnetohydrodynamic flows are known to become anisotropic under the action of a sufficiently strong magnetic field. We investigate this phenomenon in the case of low magnetic Reynolds number using direct numerical simulations and large eddy simulations of a forced flow in a periodic box. A series of simulations is performed with different strengths of the magnetic field, varying Reynolds number, and two types of forcing, one of which is isotropic and the other limited to two-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
97
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 67 publications
(118 citation statements)
references
References 21 publications
(33 reference statements)
16
97
1
Order By: Relevance
“…The main results of [6] deal with the transformation of turbulent fluctuations at intermediate and small length scales. The scale-dependent gradient anisotropy was estimated using…”
Section: Modeling Of Anisotropic Mhd Turbulence: Results Of Earlier Smentioning
confidence: 99%
See 2 more Smart Citations
“…The main results of [6] deal with the transformation of turbulent fluctuations at intermediate and small length scales. The scale-dependent gradient anisotropy was estimated using…”
Section: Modeling Of Anisotropic Mhd Turbulence: Results Of Earlier Smentioning
confidence: 99%
“…A detailed study of the anisotropy of homogeneous MHD turbulence at low R m was conducted in [6]. DNS and LES computations were performed in a wide range of Re and N .…”
Section: Modeling Of Anisotropic Mhd Turbulence: Results Of Earlier Smentioning
confidence: 99%
See 1 more Smart Citation
“…Quasi-static MHD turbulence has been studied by means of direct numerical simulation (DNS) and different tools to quantify the anisotropy have been developed so far [3]. Using energy spectra in Fourier space, it is shown that the anisotropy is persistent at small scale [4][5][6]. These spectral analyses, while capturing the multiscale character, cannot quantify the spatially intermittent nature of the flows.…”
Section: Introductionmentioning
confidence: 99%
“…The effect can also be seen in the power spectra in figure 10(c). High-q x modes are suppressed by the magnetic field and the spectrum takes the anisotropic form typical for MHD turbulence at moderate to high N (Zikanov & Thess 1998;Vorobev et al 2005). The flow evolution in the case of the one-wave initial conditions has some features reminiscent of the non-magnetic scenario (see, for example, Metcalfe et al 1987;Rogers & Moser 1992, 1993.…”
Section: Nonlinear Evolution and Transition To Turbulencementioning
confidence: 99%